PARAMETER ESTIMATION USING LEAST SQUARE METHOD FOR MIMO TAKAGI-SUGENO NEURO-FUZZY IN TIME SERIES FORECASTING - Sugiarto, Indar; Natarajan, Saravanakumar (Jurnal Teknik Elektro, 2007)
This paper describes LSE method for improving Takagi-Sugeno neuro-fuzzy model for a multi-input and multi-output system using a set of data (Mackey-Glass chaotic time series). The performance of the generated model is verified using certain set of validation / test data. The LSE method is used to compute the consequent parameters of Takagi-Sugeno neuro-fuzzy model while mean and variance of Gaussian Membership Functions are initially set at certain values and will be updated using Back Propagation Algorithm. The simulation using Matlab shows that the developed neuro-fuzzy model is capable of forecasting the future values of the chaotic time series and adaptively reduces the amount of error during its training and validation.